2019
DOI: 10.1002/masy.201800236
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Frequency Variation of Permeability for Samarium–Dysprosium–Magnesium Ferrite

Abstract: Samarium–dysprosium–magnesium ferrite materials have been prepared by chemical combustion method. The effect of samarium–dysprosium rare earth ions on loss factor, real and imaginary part of permeability has been studied for Mg[(Sm)0.6(Dy)0.4]xFe2−xO4 (x = 0.01 and x = 0.03) ferrite materials with temperature and frequency by using a Hioki LCR‐Q meter. From thermal variation of loss factor of prepared ferrite materials, it is revealed that ferrite must be used below Curie temperature for low loss factor. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…Additionally, for the frequency range of 20–10 6 Hz, we found that the relative permeability was constant for all samples. Similar results were reported in [ 62 ].…”
Section: Resultssupporting
confidence: 92%
“…Additionally, for the frequency range of 20–10 6 Hz, we found that the relative permeability was constant for all samples. Similar results were reported in [ 62 ].…”
Section: Resultssupporting
confidence: 92%